2022
DOI: 10.3389/fimmu.2022.995645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the m6ARNA gene on the prognosis of thyroid cancer, immune infiltration, and promising immunotherapy

Abstract: BackgroundAccumulating evidence suggests that N6-methyladenosine (m6A) RNA methylation plays an important role in tumor proliferation and growth. However, its effect on the clinical prognosis, immune infiltration, and immunotherapy response of thyroid cancer patients has not been investigated in detail.MethodsClinical data and RNA expression profiles of thyroid cancer were extracted from the Cancer Genome Atlas-thyroid carcinoma (TCGA-THCA) and preprocessed for consensus clustering. The risk model was construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…In the present study, we selected six independent NK cell and CD4 memory T cell summary level association results, including absolute NK cell count, NK cells/CD3-lymphocytes, NK/lymphocytes, HLA-DR+ NK AC, CD16-CD56+/NK cell. In this case, SNPs were filtered according to the procedure previously described [19]. Briefly, SNPs associated with relevant immune traits were extracted as IVs at the genome-wide significance level (P < 5.00E-6).…”
Section: Exposure Data Outcome Data and Instrument Variable Selectionmentioning
confidence: 99%
“…In the present study, we selected six independent NK cell and CD4 memory T cell summary level association results, including absolute NK cell count, NK cells/CD3-lymphocytes, NK/lymphocytes, HLA-DR+ NK AC, CD16-CD56+/NK cell. In this case, SNPs were filtered according to the procedure previously described [19]. Briefly, SNPs associated with relevant immune traits were extracted as IVs at the genome-wide significance level (P < 5.00E-6).…”
Section: Exposure Data Outcome Data and Instrument Variable Selectionmentioning
confidence: 99%
“…[19][20][21] It has also been widely applied in TC. [12,[22][23][24][25][26] With the wide application of immunotherapy in TC, a large number of related studies have emerged, accompanied by the publication of scientific papers. Bibliometrics is the application of mathematical and statistical methods to analyze data in relevant research fields.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the expression of HNRNPC is significantly elevated in TC, while WTAP, RBM15, YTHDC2, YTHDC1, FTO, METTL14, METTL3, ALKBH5, KIAA1429, YTHDF1, and ZC3H13 are remarkably decreased in tumor tissues; moreover, among these downregulated regulators, RBM15, KIAA1429, and FTO are used as a reference for prognostic analysis, which shows better performance in predicting the prognosis of TC with high accuracy [ 59 ]. This established m6A-related three-gene prognostic model is also independent prognostic markers of overall survival in TC, which modulate the key signaling pathways of TC progression, such as proteolysis and immune response [ 14 , 80 ]. It is also found that IGF2BP2, STT3A, MTHFD1, and GSTM4 could be a prognostic signature of TC patients to predict disease-free survival [ 74 ].…”
Section: Introductionmentioning
confidence: 99%